Compassion-focused therapy with autistic adults - Mason, David; Acland, James; Stark, Eloise; Happé, Francesca; Spain, Debbie (Frontiers in Psychology, 2023)
Some autistic adults experience repeated adverse events, including rejection, victimisation and stigmatisation. They also describe others being critical and negatively judging them, such as for how they socially interact or for expressing passion for particular interests. The impact of these adverse events can be substantial, including increasing vulnerability for poorer mental health, and contributing to development of negative self beliefs (such as “I am different” or “I don’t fit in”) and shame-based difficulties. Not all evidence-based psychological therapies are well-received by autistic people, or effective. Given high rates of self-harm and suicidality, finding acceptable and effective therapies for autistic adults is paramount. Here, writing as autistic and non-autistic clinicians and researchers, we outline the theoretical principles of compassion-focused theory and therapy (CFT). We propose that: (1) compassion-focused theory can provide a useful framework for conceptualising shame-based difficulties some autistic adults experience; (2) CFT can be appropriate for addressing these; and (3) there is an impetus for practitioners to adopt compassion-focused approaches when supporting autistic adults.